2004
DOI: 10.1155/2004/326767
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Helicobacter Study Group Consensus Conference: Update on the Management ofHelicobacter pylori- An Evidence-Based Evaluation of Six Topics Relevant to Clinical Outcomes in Patients Evaluated forH pyloriInfection

Abstract: As an update to previously published recommendations for the management of Helicobacter pylori infection, an evidence-based appraisal of six topics was undertaken in a consensus conference sponsored by the Canadian Helicobacter Study Group. The issues addressed and recommendations made were: bismuth-containing quadruple therapy is appropriate as an alternative first-line eradication strategy for H pylori infection; searching for and treating H pylori infection is warranted in patients considered to be at high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 42 publications
1
45
0
1
Order By: Relevance
“…However, individuals who contributed to the Asia Pacific consensus guidelines on gastric cancer prevention have suggested that guidelines for the identification and eradication of helicobacter pylori infection in Asia should be applied to Asian communities with high gastric cancer rates in Western countries (such as Korean immigrants to the US) . Additionally, Canadian Cancer Society guidelines already call for helicobacter pylori identification and eradication for Asian immigrants from high-risk countries (Canadian Cancer Society, 2014;Hunt et al, 2004). Both the physician data query screening and prevention editorial board and American society of gastrointestinal endoscopy have suggested that gastric cancer screening be considered for Asian immigrants from geographic areas with high gastric cancer incidence rates (American Society of Gastrointestinal Endoscopy, 2010;National Cancer Institute, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, individuals who contributed to the Asia Pacific consensus guidelines on gastric cancer prevention have suggested that guidelines for the identification and eradication of helicobacter pylori infection in Asia should be applied to Asian communities with high gastric cancer rates in Western countries (such as Korean immigrants to the US) . Additionally, Canadian Cancer Society guidelines already call for helicobacter pylori identification and eradication for Asian immigrants from high-risk countries (Canadian Cancer Society, 2014;Hunt et al, 2004). Both the physician data query screening and prevention editorial board and American society of gastrointestinal endoscopy have suggested that gastric cancer screening be considered for Asian immigrants from geographic areas with high gastric cancer incidence rates (American Society of Gastrointestinal Endoscopy, 2010;National Cancer Institute, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Both the Canadian helicobacter study group and Canadian Cancer Society recommend testing for and treating helicobacter pylori infection in immigrants from geographic areas of the world where the incidence of gastric cancer is high (Hunt et al, 2004;Canadian Cancer Society, 2014). The American Society of Gastrointestinal Endoscopy recognizes that helicobacter pylori identification and eradication has the potential to reduce the risk for gastric cancer in groups at high risk for the disease but does not suggest ethnicity-based deviations from usual care (American Society of Gastrointestinal Endoscopy, 2010; 2014).…”
Section: Clinical Guidelinesmentioning
confidence: 99%
“…Initially, this was a highly successful regimen, but worldwide resistance to clarithromycin has been increasing, such that treatment success is now generally 80% or less ( Figure 1). [1][2][3][4] In this article, we discuss the choice of anti-H. pylori therapies in this era of increasing antimicrobial resistance.…”
mentioning
confidence: 99%
“…Previous studies reported a success rate of >90% for bismuth-containing quadruple therapy in different parts of the world [74,75], and in Iraq [76] but, up to our knowledge, estimating the response rate and ulcer healing efficacy of H. pylori eradication according to ABO phenotypes is the first trial.…”
Section: Ulcer Healing Efficacy Of Standard Triple and Quadruple H Pmentioning
confidence: 99%